Synthesis and Crystal Structure of the First Sc‐Nb‐O‐N Phases. Issue 21 (1st June 2017) - Orthmann, Steven; Lerch, Martin
Abstract : Synthesis of phase‐pure materials in the system Sc‐Nb‐O‐N is challenging. In this contribution we report on the preparation of the first scandium niobium oxide nitrides via reaction of water‐saturated gaseous ammonia or an ammonia‐oxygen mixture with amorphous scandium niobium oxides. Two new phases were obtained: rutile‐type ScNb4 O7 N3, which crystallizes in space group P 42 / mnm, and an anion‐deficient fluorite‐type Sc2 Nb(O, N, ⬜)6 phase crystallizing in space group Fm 3 m . Abstract :